Psoriatic arthritis: epidemiological and clinical aspects in a cohort of 1.306 italian patients - L. Punzi; A. Mathieu; G. Leardini; C. Cervini; R. Scarpa (PAGEPress Publications, 2011)
Because there is the impression that psoriatic arthritis is a composite disorder with mild forms close to more severe and aggressive ones, we conducted a multicenter study with the aim of characterizing disease expression in a large cohort of Italian patients. One-thousand-three-hundred-six patients fulfilled inclusion criteria and were analyzed in this study. Psoriasis antedated the onset of arthritis in the majority of the cases (67.7%). More rare was inverse or simultaneous onset which occurred in 17.3% and 15.0% of the cases, respectively. Peripheral articular involvement (mono-oligo or polyarthritis) was recorded in 88.7% of the cases while spondylitis occurred in 11.3%. Peripheral enthesopathies were found in 28.1% of the cases with a marked occurrence in patients with axial involvement (64.5% vs 35.5% in oligo or polyarthritis). Abnormal levels of ESR and CRP respectively occurred in 52.2% and in 52.6% of the cases, while rheumatoid factor was detected in 5.0% of the cases. On the basis of distribution of joint involvement, symmetry and presence of peripheral enthesopathies we recognized three clusters of arthritis. Patients included in Cluster 1 and Cluster 2 showed a severe form of polyarthritis in most of the cases (82.9%), with increased serum levels of inflammatory indices in more than 85% of the cases. Almost all the hospitalized patients (97.1%) were included in this two clusters. They markedly assumed steroids and methotrexate or another DMARD. About half of the patients (51.1%) included in Cluster 3 showed mono-oligo articular involvement. Serum inflammatory indices were increased in 20.8% of the cases while hospitalization occurred only in 2.9% of the cases and NSAIDs were the treatment of choice. The evidence in our country of a large prevalence of severe forms of arthritis needing specific and aggressive approach outlines the requirement of an intense educational action aimed at increasing the awareness of this condition.